Difference in the Sexual and Reproductive Health of Only-Child Students and Students With Siblings, According to Sex and Region: Findings From the National College Student Survey - Zhao, Shuangyu; Liang, Yun; Hee, Jia Yi; Qi, Xinran; Tang, Kun (Frontiers in Public Health, 2022)
Objective: The differences in sexual knowledge, attitudes, behaviors, seeking behaviors for sex-related knowledge, and sexual and reproductive health (SRH) outcomes among only-child students and students with siblings in China, was examined for sex- and region- specific effects. Research Design and Methods: Data on 49,569 students from the 2019 National College Student Survey on Sexual and Reproductive Health, conducted across 31 provinces in mainland China was utilized. Multivariable regression and stratified analyses were employed to analyze the differences in sexual and reproductive health between only-child students and students with siblings. Results: Only-child students reported higher sexual knowledge, more liberal sexual attitudes, and fewer adverse SRH outcomes compared to those with siblings. Results were found to be influenced by sex and hometown region after controlling socio-economic factors, parent-child relationship, and sexuality education. Conclusions: Female students with siblings who resided in rural regions were more likely to have poorer SRH compared to male only-child students who resided in urban regions.